Lubrication behaviors of core-shell structured particles formed by whey proteins and xanthan gum. (June 2022) - Li, Borui; Gu, Wenjuan; Bourouis, Imane; Sun, Mengya; Huang, Yating; Chen, Cunshe; Liu, Xinqi; Pang, Zhihua
Abstract: Whey protein isolate and xanthan gum were used to form pure whey protein particles at 75 °C (WPI-75) or composite particles prepared at 75 °C (WPI/XG-75) and 95 °C (WPI/XG-95) to investigate the relationship between the particle characteristics and lubrication properties of biopolymer particles. A spherical core-shell structure was formed in the composite particles, wherein WPI/XG-75 showed more complete coating by XG than WPI/XG-95. WPI/XG-75 presented a similar particle size to WPI-75, while a much larger particle size was observed for WPI/XG-95. The composite particles showed higher surface hydrophobicity (H0 ) than WPI-75, with WPI/XG-75 the highest. AFM results indicated the possibility of clustering of WPI/XG-75 particles. Tribology results showed that WPI/XG composite particles exhibited a rather higher friction coefficient than WPI-75 during the initial sliding, due to the particles clustering or the large particle size. However, similar or even lower friction was observed with WPI/XG-95 than WPI-75 when the sliding speed was over 0.5 mm/s. Particles with or without XG showed different lubricating behaviors with the presence of artificial saliva. WPI/XG-95 was also found to exhibit excellent fat replacing function in the o/w emulsion. Thus, particles with core (WPI)-shell (XG) structure are very promising in fat replacement. However, particle size and particle clustering issue need to be further improved. Graphical abstract: Image 1 Highlights: Spherical core-shell structured particles with different particle sizes were formed. WPI/XG-75 showed the highest surface hydrophobicity and possible particle clustering. WPI/XG-75 and WPI-75 showed different lubricity with presence of artificial saliva. WPI/XG-95 showed excellent fat replacing effect in o/w emulsions.